Inflammatory bowel disease and the risk of intracerebral hemorrhage: A Mendelian randomization study and meta‐analysis - Yanju Song; Xuelun Zou; Yi Zeng; Le Zhang; Xinfa Mao (Immunity, Inflammation and Disease, 2023)
Abstract Background The link between inflammatory bowel disease (IBD) and intracerebral hemorrhage (ICH) is still unclear. Aims We conducted a Mendelian randomization research and meta‐analysis to explore the impact of IBD and its subtypes (Crohn's disease [CD], ulcerative colitis [UC]) on the risk of ICH. Methods Two large genome‐wide association analysis studies of International Inflammatory Bowel Disease Genetics Consortium (IIBDGC) and International Stroke Genetics Consortium as exposure (IBD, UC, and CD) and outcome (ICH) in the initial stage. IBD, CD, UC GWAS data from the FinnGen consortium were adopted for the replication phase, and ultimately, the results of the initial stage and replication phase data were combined in a meta‐analysis to evaluate the causal association between IBD and its subtypes and the risk of ICH. Results In the initial stage, we found that in the IVW (odds ratio [OR] = 0.83, 95% confidence interval [CI]: 0.71–0.96, p = .01), MR‐PRESSO (OR = 0.85, 95% CI: 0.75–0.97, p = .02) and MR.RAPS (OR = 0.86, 95% CI: 0.76–0.98, p = .02) method showed that UC is associated with the risk of ICH. The causal relationship between IBD, CD, and the risk of ICH cannot be found by the IVW method. IBD and its subtypes UC, CD, and risk of ICH cannot find the presence of heterogeneity and pleiotropy. In replication stage, IBD (OR = 0.74, 95% CI: 0.59–0.94, p = .0135) related to ICH, while the IVW approach did not establish a causal link in UC and CD. The meta‐analysis still indicated that UC (OR = 0.83, 95% CI: 0.72–0.93, p < .05) would lessen the risk of ICH while the causality between IBD, CD, and ICH was unable to be established. Conclusion UC was causally related to ICH, but IBD and CD are not associated with ICH. The precise pathophysiological mechanism needs to be thoroughly investigated in more detail.